A Decision Analysis of Observation vs Immediate Reintervention for Asymptomatic Residual Fragments Less than 4 mm Following Ureteroscopic Lithotripsy. Issue 5 (September 2019) - Ursiny, Michal; Yaghoubian, Alan; Humphreys, Mitchell R.; Brotherhood, Hilary; Chew, Benjamin H.; Monga, Manoj; Krambeck, Amy E.; Charchenko, Cameron; Wang, An Qi; Sur, Roger L.; Miller, Nicole L.; Marien, Tracy; et al.
Abstract: Introduction: We performed a decision analysis model of the cost-effectiveness of observation vs intervention for asymptomatic residual fragments less than 4 mm in diameter following ureteroscopic holmium laser lithotripsy. Methods: Outcomes data from a retrospective analysis evaluating the natural history, complications and reintervention rates of asymptomatic residual stone fragments performed by the EDGE (Endourology Disease Group for Excellence) Research Consortium were used. A decision analysis model was constructed to compare the cost-effectiveness of initial observation of residual fragments to immediate intervention. Cost of observation included emergency room visits, hospitalizations and reinterventions. The cost analysis model extended to 3 years to account for delayed reintervention rates for fragments less than 4 mm. Costs of emergency department visits, readmissions and reinterventions were calculated based on published figures from the literature. Results: Decision analysis modeling demonstrated that when comparing initial observation to immediate reintervention, the cost was $2, 183 vs $4, 424. The difference in cost was largely driven by the fact that over 3 years, approximately 55% of all patients remained asymptomatic and did not incur additional costs. This represents an approximate annual per patient savings of $747, and $2, 241 over 3 years when observation is selected over immediate reintervention. Conclusions: Our decision analysis model demonstrates superior cost-effectiveness for observation over immediate reintervention for asymptomatic residual stones less than 4 mm following ureteroscopic lithotripsy. Based on these findings careful stratification and selection of patients may enable surgeons to improve cost-effectiveness of managing small, asymptomatic residual fragments following ureteroscopic lithotripsy.